Detection of sensitive soil properties related to non-point phosphorus pollution by integrated models of SEDD and PLOAD. (January 2016) - Lin, Chen; Wu, Zhipeng; Ma, Ronghua; Su, Zhihu
Graphical abstract: Highlights: We developed an integrated model for non-point source P loads assessment in rapid urbanization area. Some key parameters in the model were measured in situ to improve the robustness of the modeling. The critical soil properties were identified for non-point dissolved P and particulate P losses. Abstract: Effectively identifying soil properties in relation to non-point source (NPS) phosphorus pollution is important for NPS pollution management. Previous studies have focused on particulate P loads in relation to agricultural non-point source pollution. In areas undergoing rapid urbanization, dissolved P loads may be important with respect to conditions of surface infiltration and rainfall runoff. The present study developed an integrated model for the analysis of both dissolved P and particulate P loads, applied to the Meiliang Bay watershed, Taihu Lake, China. The results showed that NPS P loads up to 15 kg/km 2 were present, with particulate P loads up to 13 kg/km 2 . The highest loads were concentrated in the southeastern region of the watershed. Although particle P was the main contributor to NPS P loads state, the contribution of dissolved P was significant, especially in sub-basins with significant amount of artificial land cover. The integration of dissolved P and particulate P loads provided more accurate evaluation of NPS P pollution. NPS P loads were found to correspond to specific soil properties. Soil organic matter and total nitrogen were shown to influence dissolved P loads, while total phosphorus and soil particle composition proportion were more closely related to particulate P loads.